2022
DOI: 10.1155/2022/1153208
|View full text |Cite|
|
Sign up to set email alerts
|

Blockchain and K-Means Algorithm for Edge AI Computing

Abstract: The current development of blockchain, technically speaking, still faces many key problems such as efficiency and scalability issues, and any distributed system faces the problem of how to balance consistency, availability, and fault tolerance need to be solved urgently. The advantage of blockchain is decentralization, and the most important thing in a decentralized system is how to make nodes reach a consensus quickly. This research mainly discusses the blockchain and K-means algorithm for edge AI computing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The distance is typically used to compare and contrast the characteristics of different data objects. The typical K-Means algorithm uses K = 2, meaning that it clusters data into pairs; when K equals 1, the K-Means algorithm in this study is enhanced, K's coordinates were found and then the nodes that form the cluster with K and those that are not in it were identified [23,24]. Given that we wish to search for a particular group of stores, the enhanced K-Means (EK-M) algorithm fits the concept of a market; the necessary product is available, and these stores are conveniently located; the location of customer represents the location of K. Based on the Euclidean Distance, the EK-M algorithm calculates the distance between two points.…”
Section: Enhanced K-means Clusteringmentioning
confidence: 99%
“…The distance is typically used to compare and contrast the characteristics of different data objects. The typical K-Means algorithm uses K = 2, meaning that it clusters data into pairs; when K equals 1, the K-Means algorithm in this study is enhanced, K's coordinates were found and then the nodes that form the cluster with K and those that are not in it were identified [23,24]. Given that we wish to search for a particular group of stores, the enhanced K-Means (EK-M) algorithm fits the concept of a market; the necessary product is available, and these stores are conveniently located; the location of customer represents the location of K. Based on the Euclidean Distance, the EK-M algorithm calculates the distance between two points.…”
Section: Enhanced K-means Clusteringmentioning
confidence: 99%
“…represents the degree to which x i belongs to the kth class [26][27][28][29][30][31][32][33][34][35][36][37]. e algorithm framework of FCM is shown in Figure 2.…”
Section: Fuzzy C-means Rough Setmentioning
confidence: 99%
“…FCM is an extension of the traditional K-means algorithm, which continuously updates the membership degree by minimizing the intra-class spacing. When the membership degree of all objects to all classes is determined, the class with the largest membership degree is selected as the class to which the object belongs [26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Fuzzy C-means Rough Setmentioning
confidence: 99%
“…e customer segmentation technology based on a clustering algorithm has been applied in various areas as early as the 19th century, such as retail, financial stocks, banking, e-commerce, telecommunications, tourism, aviation, and other industries. e similarity function of the K-means algorithm is mainly determined based on the distance between the data, and the distance measurement method constitutes the primary method of clustering [25][26][27]. e algorithm in this paper adopts the Euclidean distance because the Euclidean distance is mostly used to analyze individual differences in values, such as using user behavior indicators to analyze the similarity of user values.…”
Section: Improvement Of Clustering Algorithm Based On K-meansmentioning
confidence: 99%